HAK TERSANGKA UNTUK MENDAPATKAN BANTUAN HUKUM DALAM PROSES PENYIDIKAN - Diah Safitri, Maya; Sutama, Ida Bagus Putu (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 01, Maret 2014)
The right to obtain legal aid to suspects especially the underprivileged, can be obtained at any stage of the examination, one of them at this stage of the investigation. In this study, there are two problems have been studied, that is how the urgency of the right of suspects to obtain legal aid and legal consequences if a suspect haven’t accompanied by legal counsel in any investigation process. The method used in this paper is the use of normative legal research because there are still obscurity norms about “the right time and at any level of examination, according to the procedures which regulated in the Act". Discussion of these issues are providing legal assistance in the investigation process relating to the presumption of innocence who that every person can’t be found guilty if not legally enforceable and the legal consequences if the suspect hasn’t accompanied by legal counsel in the investigation process in MA RI Decision No.1565 K / Pid/1991, consequently, Prosecution demands can’t be accepted because the right mentoring is imperative nature of rights, which if neglected will result in invalidity of the examination process. The conclusion of this study are urgency right to legal assistance in any investigation process is very important because as a fundamental right of a suspect who governed by the Act, which if neglected will make the process of checking unauthorized and non-acceptance of the demands of the public prosecutor.
Keywords: HAK TERSANGKA UNTUK MENDAPATKAN BANTUAN HUKUM DALAM PROSES PENYIDIKAN